STRATEGI KOMUNIKASI WISATA RELIGIUS DALAM MENINGKATKAN JUMLAH KUNJUNGAN WISATA OLEH BADAN PENGELOLA MASJID AGUNG ISLAMIC CENTRE ROKAN HULU - Candra, : Ardinal; ", Nurjanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Objectives of the study are to analyze the communications strategy based religious tourism in increasing the number of tourist visits by the Board of Mosque Management Grand Mosque of Rokan Hulu Center. In addition, this study also wants to know the strategy communicators, audience strategies, messaging strategies, media strategies and effects arising from communication strategies used by the Management Agency. This research uses qualitative method with descriptive study. Technique of collecting data from this research through interview, observation, and documentation. Communication Strategy Management Agency in increasing the number of tourist visits at the Great Mosque Islamic Center Rokan Hulu good enough. Implementation of communication strategy Management Board communicators have credibility, knowledge, and experience, khalayakan target is the community and the group with the message conveyed the message informative and persuasive. The governing body uses several mass media such as television, radio, billboards and others. The effect of this communication strategy is the improvement and reduction of tourism based on the satisfaction of visitors to the Board of Mosque Management Grand Mosque of Rokan Hulu Center. Keywords: Communication Strategy, religious tourism, and Management Board